Evolving identities in popular culture. Issue 1 (27th December 2022) - Piatti-Farnell, Lorna; Peaty, Gwyneth; Prosser, Ashleigh
In our twenty-first century context, we tell stories through the foods we eat, the images we share, the people we follow on social media, the shows we watch and the music we listen to. From film to television, from Twitter accounts to the latest fandom trend, popular culture provides us with channels through which our narratives of everyday can transform from immaterial notions to very material and tangible objects of consumption. At the centre of our ways of storytelling lies the formation of our identities. This editorial introduces a Special Issue of the Australasian Journal of Popular Culture that is focused on exploring the many complex intersections between storytelling, identity and popular culture.